Distinction between the Preneoplastic and Neoplastic State of Murine Mammary Glands - Hazlewood, C. F. (1972)
We have, using nuclear magnetic resonance spectroscopy, measured the relaxation times and diffusion coefficient of water protons in primary mammary adenocarcinomas of mice. In our biological model, three morphological stages were defined: (a) mammary gland tissue from pregnant mice, (b) preneoplastic nodules, and (c) neoplastic tissue. It was found that neoplastic tissues could be distinguished from normal and prenoeplastic tissue. Spin-spin and spin-lattice relaxation times and the diffusion coefficient of water protons are increased in the neoplastic tissue relative to mammary gland tissue from pregnant mice and preneoplastic nodule tissue.